Efeitos do treinamento aeróbio aquático na pressão arterial, aptidão física e qualidade de vida em idosos recuperados pós-covid-19 - Gurginski, Renata Neli Moreno (2022)
Introduction: About one in five people will experience prolonged symptoms after being diagnosed with COVID-19. Prolonged symptoms have affected severe patients and even those who had mild manifestations, limiting day-to-day activities and impairing quality of life. An exercise program in a liquid environment has advantages over the terrestrial environment, where a comfortable and safe environment is provided for exercising, making it relevant to consider for the post-covid-19 population. It is assumed that an aquatic aerobic training program will improve physiological responses and quality of life in people recovered from COVID-19 contamination. Methods: 22 elderly convalescents from mild to moderate COVID-19 participated in a 10-week aquatic aerobic training program of progressive intensity 3 times a week, totaling 30 sessions. For intensity progression, the BORG intensity scale was used. Sessions had 5 minutes of warm-up and 5 minutes of cool-down and were composed of up to eight exercises that worked with large lower and upper muscle groups. Results: Significant results were found for the sit and stand tests (PRE 12.00 ± 3.21 POST 14.19 ± 4.31) (p=0.004) and forearm flexion (PRE 17.10 ± 3.48 POST 19.86 ± 3.57) (p=0.002). For BP, quality of life and cognition assessments, no significant results were found. Conclusion: It is suggested that aquatic aerobic training with progressive intensities for a population convalescing from mild to moderate COVID-19 can increase upper and lower limb strength, reflecting an improvement in physical fitness. In this applied model, no results were obtained in BP, quality of life and cognition, so more investigations must be carried out to fill the gap in the literature of training programs for this population. The limitations of the present study are due to the absence of a control group.